Evaluating predictors of local dabbling duck abundance during migration: managing the spectrum of conditions faced by migrants - Aagaard, Kevin; Crimmins, Shawn M.; Thogmartin, Wayne E.; Tavernia, Brian G.; Lyons, James E. (Wildfowl, 2015)
The development of robust modelling techniques to derive inferences from largescaleÂ migratory bird monitoring data at appropriate scales has direct relevance to theirÂ management. The Integrated Waterbird Management and Monitoring programmeÂ (IWMM) represents one of the few attempts to monitor migrating waterbirds acrossÂ entire flyways using targeted local surveys. This dataset included 13,208,785 waterfowlÂ (eight Anas species) counted during 28,000 surveys at nearly 1,000 locations across theÂ eastern United States between autumn 2010 and spring 2013 and was used to evaluateÂ potential predictors of waterfowl abundance at the wetland scale. Mixed-effects, loglinearÂ models of local abundance were built for the Atlantic and Mississippi flywaysÂ during spring and autumn migration to identify factors relating to habitat structure,Â forage availability, and migration timing that influence target dabbling duck speciesÂ abundance. Results indicated that migrating dabbling ducks responded differently toÂ environmental factors. While the factors identified demonstrated a high degree ofÂ importance, they were inconsistent across species, flyways and seasons. Furthermore,Â the direction and magnitude of the importance of each covariate group consideredÂ here varied across species. Given our results, actionable policy recommendations areÂ likely to be most effective if they consider species-level variation within targetedÂ taxonomic units and across management areas. The methods implemented here canÂ easily be applied to other contexts, and serve as a novel investigation into local-levelÂ population patterns using data from broad-scale monitoring programmes.